2016
DOI: 10.1002/acr.22904
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Perceptions of Lupus Medication Decision‐Making Facilitators: The Importance of Patient Context

Abstract: Consideration of how different stakeholders perceive the relative importance of lupus medication decision-making clusters is an important step toward improving patient-physician communication and effective shared decision-making. The empirically derived framework of medication decision-making facilitators can be used as a guide to develop a lupus decision aid that focuses on improving physician-patient communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…It was tailored to the target population’s numeracy and health and graphical literacy levels [36]. It incorporated barriers to and facilitators of medication decision-making in women with lupus nephritis [2224] and the CER data on medication benefits and risks [2527]. Themes generated from nominal groups of patients with lupus nephritis, including African-American, Hispanic, Asian, and white women [2224], were incorporated into the decision aid content and presentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was tailored to the target population’s numeracy and health and graphical literacy levels [36]. It incorporated barriers to and facilitators of medication decision-making in women with lupus nephritis [2224] and the CER data on medication benefits and risks [2527]. Themes generated from nominal groups of patients with lupus nephritis, including African-American, Hispanic, Asian, and white women [2224], were incorporated into the decision aid content and presentation.…”
Section: Methodsmentioning
confidence: 99%
“…It incorporated barriers to and facilitators of medication decision-making in women with lupus nephritis [2224] and the CER data on medication benefits and risks [2527]. Themes generated from nominal groups of patients with lupus nephritis, including African-American, Hispanic, Asian, and white women [2224], were incorporated into the decision aid content and presentation. Because we recruited similar target patient populations for the nominal groups and the trial (those from racial/ethnic minority groups with low socioeconomic status [SES] or low literacy), themes and content generated were culturally tailored to included populations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlights similar findings documented in previous studies. As patients with SLE are often anxious and misinformed regarding their disease, clinicians play an important role in educating and communicating with patients in order to maximize medication adherence and improve health outcomes . A few qualitative studies have identified that coordinated, collaborative care is valued in managing multisystem diseases, such as osteoporosis and diabetes mellitus , and working in multidisciplinary care provided reassurance to health care professionals regarding their clinical decisions .…”
Section: Discussionmentioning
confidence: 99%
“…Stratification by clinical and serological phenotypes , demography and habits is qualitative, on disease activity measures quantitative 50–57. Stratification on sex, race, socioeconomic status,58–62 access to medical care, medication choice and adherence,63 willingness to participate in clinical trials, doctor–patient interactions,64 patient preferences and perceptions,65 lifestyle choices,66 67 physician choices,68–71 environmental triggers,72–76 poverty,77 social disparities,78 and life events,79 smoking80 and the gut pathobiont81 all affect manifestations and outcomes in ways that dictate who participates in a study on SLE and in ways that cannot be examined in animal models 82. Stratification on gene expression , quantitative, predicts risk and possibly phenotype83–93; SLE-like illnesses (the autoinflammatory diseases),94 Aicardi-Goutières syndrome,95 96 Canale-Smith syndrome97 and SLE associated with immunodeficiency98 suggest mechanisms for primary illness, and for phenotype diversity.…”
Section: Stratificationmentioning
confidence: 99%